PENGGUNAAN ZAKAT PRODUKTIF UNTUK MEMBERDAYAKAN MASYARAKAT MUSLIM PENYANDANG DISABILITAS (KAJIAN DARI UU NO. 8 TAHUN 2016 DAN NO. 23 TAHUN 2011) - Agus Rianto (Journal of Law, Society, and Islamic Civilization, 2016)
Every human being wants to be born in normal circumstances, but for various reasons not a few people she encountered a defect in a wide range, so that they become disabled / disability. In society, based on Law No. 8 2016 About Disability, they still have rights and obligations equal to those of normal.They must be given help and empowerment, for people with disabilities / disability, referring to the Law No. 8 Year 2016 About Disability, have the same right to a decent living. There are some other products that Act provides protection to the rights of persons with disabilities, such as Law No. 23 Years 2011Tentang Zakat Management.For Muslims disability / disability, when referring to the Law No. 23 Year 2011 concerning the Management of Zakat eligible for assistance from the zakat fund, donation and charity, especially Zakat on Earning to empower their lives for the benefit of themselves and society. Especially help it, when referring to Law No. 8 2016 above, can be provided as capital that can be used to earn a living and develop the potential of people with disabilities / disability.Keywords: disabled / disability, zakat on earning, empowerment, venture capital